Analyzing the cooperative growth of intermetallic phases with a curved solidification front. (15th October 2018) - Nani, E.S.; Nestler, Britta; Ankit, Kumar
Abstract: The classical Jackson-Hunt (JH) relation is re-derived to incorporate the physics of curved solid-liquid interfaces on the lamellar growth kinetics of binary intermetallic eutectics. A semi-analytical approach is adopted to explore the entire range of compositions within the miscibility gap. The interface shape calculation implemented in the classical theory is interpreted as a first step in an iterative process which can be carried through to convergence within the framework of the current extended analysis thus rendering the theory self-consistent and, except for the triple junction angles that have to be input, self-contained. The influence of the low péclet number approximation on the kinetics relation is thoroughly analyzed. It is found that the relative error in velocity due to this approximation scales with péclet number and is independent of the shape of the solid-liquid interface profile. Growth kinetics of NiZr-NiZr2 lamellar eutectics predicted by the modified theory are compared with those of the classical JH theory. Graphical abstract: Image 1